Blueprint : measuring sustainable development - Pearce, David (London, 1993)
Blueprint 3 is the direct sequel to the ground-breaking Blueprint for a Green Economy. Taking the argument much further, David Pearce and his colleagues show how progress towards sustainability in the UK can be measured. They set out the conditions for sustainable development and the measures of economic progress these imply, before looking in detail at all the main areas of economic activity to which the measures are applicable. The result is a wide-ranging and cogent critique of existing policies which also offers new options - options which will require far-reaching reform of this country's existing political and institutional structure. Blueprint 3 will be a touchstone for future discussions of all the major policy areas.
Keywords: Sustainable development